Dark Tourism in Colombia: Motivation of Travellers and Community Practices. - Mora Forero, Jorge Alexander; Bohórquez Patino, Luis Mauricio; León-Gómez, Ana María (Editura Universitati din Oradea, 2022)
Based on the infamous case of the natural disaster of the Armero volcano eruption, this study aims to analyze the perception of the local community towards the development of dark tourism. In particular, the main central question to be addressed in this article is to examine the motivation of tourists and the perception of local residents towards the tourism activity related to this event. To this end, a qualitative methodology was adopted through observation and interview. Our results show that the main motivation of tourists visiting the Armero region is the curiosity to see other people's deaths. However, his feelings change after visiting this region, as curiosity turns to sadness at seeing the suffering of so many people. On the other hand, some locals are not pleased that their history and heritage revolve around tragedy and the dead. This study highlights the lack of awareness of this type of tourism. It is therefore necessary that governments and competent authorities implement measures to encourage the development of this type of tourism. In this way, the cultural impact of black tourism in Colombia can be improved.
Keywords: Turismo - Colombia - Aspectos sociales; Colombia; Armero; Tourism; Dark tourism; Disaster